2011
DOI: 10.1128/aem.01829-10
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence-Based Method for Measuring Assimilable Organic Carbon in Pretreatment Water for Reverse Osmosis Membrane Desalination

Abstract: A bioluminescence-based assimilable organic carbon (AOC) test was developed for determining the biological growth potential of seawater within the reverse osmosis desalination pretreatment process. The test uses Vibrio harveyi, a marine organism that exhibits constitutive luminescence and is nutritionally robust. AOC was measured in both a pilot plant and a full-scale desalination plant pretreatment.In the desalination industry, reverse osmosis (RO) membrane fouling from biological growth, i.e., biofouling, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 4 publications
4
33
0
1
Order By: Relevance
“…A recent work [24] showed the feasibility of using the naturally occurring luminous strain, V. harveyi BB721, in AOC assays for saline water samples. The strength of luminescence signals of the microbial biomass yielded were significantly related to the amount of organic carbon added.…”
Section: Discussionmentioning
confidence: 99%
“…A recent work [24] showed the feasibility of using the naturally occurring luminous strain, V. harveyi BB721, in AOC assays for saline water samples. The strength of luminescence signals of the microbial biomass yielded were significantly related to the amount of organic carbon added.…”
Section: Discussionmentioning
confidence: 99%
“…It was in the studies on the regions where microbial growth in drinking waters was regulated by the content of phosphorus, rather than organic carbon [52][53][54] was developed. In the studies on reclaimed water and desalination of seawater, Weinrich et al [31] built the AOC bioassay with the bioluminescent derivatives of P17 and NOX as inoculum for reclaimed water and another AOC bioassay [30] with V. harveyi suitable for sea water. Moreover, further developments [9,41,55] have demonstrated that at these low AOC concentrations the attached bacterial (biofilms) growth occurs at very short contact times.…”
Section: Applications Of Aoc Bioassaymentioning
confidence: 99%
“…According to Hammes' [19] study, total cell count with fluorescence staining and flow cytometry replaced plate count method can be used to establish complete growth curves for a natural microbial consortium growing on AOC. Weinrich et al [30] used Vibrio harveyi, a marine organism that exhibits constitutive luminescence suitable for sea water and is nutritionally robust as AOC bioassay inoculum without construction of Table 3 The AOC values of water samples from three methods (cited from the paper of Liu [ bioluminescent AOC assay strains. Especially, the use of V. harveyi expanded the application field of AOC from freshwaters to seawater.…”
Section: Evolution Of Bacterial Growth Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…A common species of marine bacteria, Vibrio harveyi was used as model seawater bacteria. This species has been used as a standard bacterium for measuring assimilable organic carbon (AOC) in seawater (Weinrich et al, 2011). A pure strain of the bacteria (NCCB 79042) was inoculated in sterilised saline (34 g/L) medium for lucibacterium and incubated at 30 o C until the concentration reach ~100 million cells/ml.…”
Section: Marine Bacteriamentioning
confidence: 99%